Instruction and re-education: wich role for the school in prison? - Cardinali, Cristiana; Craia, Rodolfo (Formazione & insegnamento, 2016)
The substantial, direct relationships between the two different systems of Education and Prison are determined not only by the respective institutional roles within the social structure of a country, but also (and especially) by the key principles that inspire their pedagogical and (re)educational mission. This reflection on the educational and social goals that the school-to-prison system should/could achieve extends their roles beyond the mere consideration of the prison as containment and punishment apparatus and of the school as an “obligation”. Moreover, the analysis of these facets of the topic reinforce the opportunity of a new idea of mutual scaffolding between all interacting for a shared load outlet, a proposal that implicate an analysis of the topic from the inside to the outside of the prison walls. Therefore, among the activities aimed at the social rehabilitation of prisoners, Education appears to be an essential element of intervention in the prison context, in addition to represent an essential tool for supporting the process of personal growth. Consequently, this individual development and empowerment encourages the inmates to abandon the negative values, that generate deviant behavior, in favor of positive social reintegration. In the light of the recent legislation that sanctioned the specificity of formative path held inside the prisons, this article contributes to the analysis of the existing situation by presenting operative and planning models actually tested in a penitentiary of an Italian province.